Alteration of Plant Primary Metabolism in Response to Insect Herbivory. Issue 3 (16th September 2015) - Zhou, Shaoqun; Lou, Yann-Ru; Tzin, Vered; Jander, Georg
Abstract : The species and feeding habits of insect herbivores influence the changes in photosynthesis, carbon allocation, and nitrogen utilization that are observed in host plants. Abstract: Plants in nature, which are continuously challenged by diverse insect herbivores, produce constitutive and inducible defenses to reduce insect damage and preserve their own fitness. In addition to inducing pathways that are directly responsible for the production of toxic and deterrent compounds, insect herbivory causes numerous changes in plant primary metabolism. Whereas the functions of defensive metabolites such as alkaloids, terpenes, and glucosinolates have been studied extensively, the fitness benefits of changes in photosynthesis, carbon transport, and nitrogen allocation remain less well understood. Adding to the complexity of the observed responses, the feeding habits of different insect herbivores can significantly influence the induced changes in plant primary metabolism. In this review, we summarize experimental data addressing the significance of insect feeding habits, as related to herbivore-induced changes in plant primary metabolism. Where possible, we link these physiological changes with current understanding of their underlying molecular mechanisms. Finally, we discuss the potential fitness benefits that host plants receive from altering their primary metabolism in response to insect herbivory.